TINUNGGLU’S GOVERNING : TRADITIONAL FOOD BUFFER SYSTEM IN MENTAWAI AS GOVERNANCE - Rijel Samaloisa; Munawar Ahmad; Ati Ataul Qudus; Happy Nurdiana Tatubeket (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2023)
This paper elaborates on Tacit-governing food buffer systems in Mentawai island, Tinungglu. Tinungglu is the old system of agriculture system of the Mentawai People, especially on Siberut Island. its role as a buffer stock food system when their life is in a vulnerable situation. This analysis focused on looking at three significant sets of variables contributing to the governability of societal entities, including the natural resources valued by those entities: those entities considered a system-to-be-governed (SG), those governing these entities, labeled the governance system (GS), and the interrelation between these two, worked out in terms of governing relations or interactions (GI). Finally, its results identify the area of governability whereas the intersection among government and traditional systems on tinungglu.